PAIN AND DISCOMFORT DURING AGRICULTURAL TRACTORS OPERATION (Fiep Bulletin - online, 2013)
Agricultural mechanization brought the machines in order to replace animal traction, improving the productivity and profitability at work. However, with the high speed of mechanization, the workers need to be updated to deal with the machinery, once that they start using them without the right training, leading to accidents in the field and inappropriate posture. The majority of low back pain cases can be caused by the prolonged sustenance of static posture, stabilizing the body to make movements in speed, which is also very common in agricultural workers. The aim of this study is to verify the existence of relation between pain and discomfort associated with daily working hours of agricultural tractor operators. Data collection was performed during Show Rural Coopavel, 2008 in the city of Cascavel PR, 188 agricultural tractor operators from the West region of Parana, were interviewed through a questionnaire of direct application. The results showed that 89,96% of these workers remain more than seven hours a day on the machine, conscious that they are not sitting properly during work, presenting high levels of pain/discomfort, and the most affected places were: the lumbar spine, neck, back and legs. The chi-square test shows that there are significant relations among fatigue, daily working hours and pain and discomfort levels. It can be concluded that the sustenance of the sitting position for long periods, especially in inappropriate postures, can interfere in the appearance of pain and discomfort in farm workers, and the parts of the body most mentioned are those used for static posture sustenance.
Keywords: Sitting Positions at work; Posture; Ergonomics